PENGELOLAAN PASCA PANEN BUAH KELAPA TERINTEGRASI BAGI MASYARAKAT LOKAL DI KAMPUNG MOPAH LAMA DISTRIK MERAUKE - Mangera, Yosefina; Andriyono, Andriyono; Ponadi, Acep (Jurnal Abdi Insani, 2025)
The local community in Kampung Mopah Lama has a coconut plantation that is managed independently and independently using traditional equipment. Management of the coconut harvest is still carried out in a traditional way by selling and marketing the coconuts in logs/whole including the coconut fiber and shell. In terms of economic calculations, a whole sales system will greatly reduce its economic value. The purpose of this activity is to introduce coconut post-harvest equipment to the Kokoti farmer group in order to increase the productivity of coconut product marketing in the form of product diversification so that it can increase the added value of coconut fruit products owned by the community. The method used in this PKM activity is the socialization and training of the operation of coconut post-harvest machines which include coconut fiber peeling machines, coconut shell/shell peeling machines and coconut fiber decomposing machines into cocopit. The result of this activity is that the Kokoti farmer group has additional insight into the diversification of coconut harvest products and is skilled in operating coconut post-harvest machines. The application of this technology is expected to be able to support the government's national program in advancing small and medium industries, so that it is hoped that the availability of this technology will be able to trigger the development of household industries.